Media. - Becker, Wolfgang; Teuteberg, Gabriele (Aachen : Ludwig Forum für Internationale Kunst Aachen, 1991)
Abramovic, Marina & Ulay ; Anderson, Laurie ; Arakawa, Shusaku ; Artschwager, Richard ; Baldessari, John ; Baumgarten, Lothar ; Becher, Bernd & Hilla ; Bechtle, Robert ; Beckers, Günther ; de Beeck, Felix van ; Beuys, Joseph ; Blume, Anna & Bernhard Johannes ; Brecht, George ; Brehmer, Klaus-Peter ; Brock, Bazon ; Bruch, Klaus vom ; Burden, Chris ; Campus, Peter ; Christiansen, Henning ; Christo ; Clark, Gordon Matta ; Close, Chuck ; Dahn, Walter ; Davis, Douglas ; Dibbets, Jan ; Dokoupil, Jiri Georg ; Eddy, Don ; Estes, Richard ; Favier, Philippe ; Fischli & Weiss ; Fox, Terry ; Fulton, Hamish ; Gac, Jean Le ; Gasiorowski, Gérard ; Gertsch, Franz ; Gerz, Jochen ; Gilbert & George ; Goings, Ralph ; Graves, Nancy ; Gusella, Ernest ; Hamilton, Richard ; Hays, Ron ; Heibach, Astrid ; Heizer, Michael ; Hendricks, Geoffrey ; Hoffmann, Martin ; Hoover, Nan ; Horn, Rebecca ; Hucleux, Jean Oliver ; Iannone, Dorothy ; Inoue, Bukichi ; Jonas, Joan ; Kagel, Mauricio ; Kahlen, Wolf ; Knoebel, Imi ; Kubisch, Christina ; Kushner, Robert ; Lakner, Laszlo ; Leisgen, Barbara & Michael ; Long, Richard ; de Maria, Walter ; Matos, John ; Mau, Jürgen ; Monory, Jacques ; Morris, Robert ; Nauman, Bruce ; Nicolas, Jean Michel ; Odenbach, Marcel ; Paik, Nam June ; Pitt, Susan ; Plessi, Fabrizio ; Rauschenberg, Robert ; Richter, Gerhard ; Rosenbach, Ulrike ; Sarkisian, Paul ; Schoofs, Rudolf ; Serra, Richard ; Sharits, Paul ; Simonds, Charles ; Smithson, Robert ; Snow, Michael ; Sonfist, Alan ; Sonnier, Keith ; Stenvert, Curt ; Vostell, Wolf ; Walker, Willie ; Warhol, Andy ; Wegman, William ; Wesselman, Tom
biografie, bibliografie
Media, Ludwig Forum für Internationale Kunst, Aachen, 29.6.1991 - 22.9.1991
Duits
boek